Quantitative melissopalynological analysis of bee honey using a Bürker chamber - Dinkov, D. (2017)
The article describes a new proposal for quantitative melissopalynological analysis of pollen grains in 10 g bee honey, using a Bürker chamber for peripheral white blood cells counting. The research related to the development of the method and its algorithm are presented. Further investigations in certified laboratories are required to evaluate the repeatability and reproducibility of the method for “under-represented”, “normal-represented” and “over-represented” bee honeys.